Glycerol Valorization Towards Glycolic Acid Production Over Cu‐Based Biochar Catalyst. Issue 23 (27th October 2022) - Liao, Shengqi; Tian, Qing; Xiao, Yuan; Qin, Diyan; Li, Jianmei; Hu, Changwei
Abstract: Glycerol valorization towards high‐value chemicals is of particular importance to increase the value chain of biodiesel production. In this study, the catalytic activity of a series of cheap Cu‐based catalysts for glycerol conversion is investigated. Cu supported on activated carbon (AC, obtained through carbonization of coconut shell) exhibits outstanding catalytic activity for the selective conversion of glycerol into glycolic acid (GcA) in O2 atmosphere, affording up to 68.3 % GcA yield. The combination of experimental results with theoretical calculations reveals that glyceraldehyde is the key reaction intermediate. The high specific surface area and surface oxygenated groups of AC enable the formation of CuO nanoparticles with small size and uniform dispersion. In addition, the surface oxygen vacancy on Cu/AC might help to activate reaction intermediates, and the electron transfer from Cu to AC facilitates the oxidation of glycerol to GcA. Cu loaded onto AC also significantly inhibits C−C breakage to generate formic acid as a byproduct. This work might aid the development of approaches for glycerol application and afford profitable possibilities for sustainable biodiesel. Abstract : GcA genius : Conversion of glycerol into glycolic acid is achieved over an activated carbon‐supported Cu catalyst with up to 68.3 % yield. This method might aid the development of approaches for glycerol application and afford profitable possibilities for sustainable biodiesel.